2003
DOI: 10.1007/s00101-003-0474-2
|View full text |Cite
|
Sign up to set email alerts
|

Ausgeprägte Hyperthermie und Rhabdomyolyse nach Ecstasy (MDMA)-Intoxikation

Abstract: Abuse of 3,4-methylenedioxymethamphetamine (MDMA,Ecstasy) is still growing over the last years and reports of severe or even fatal complications, such as arrhythmias, hyperpyrexia, rhabdomyolysis, disseminated intravascular coagulopathy (DIC), acute renal or liver failure or brain oedema are also increasing. We report the case of a 21-year-old male who took a suicidal overdose of MDMA and subsequently developed severe hyperpyrexia (>43 degrees C/109.4 degrees F), rhabdomyolysis with an initial myoglobin level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…It has been reported that body temperature may reach up to 43°C, which can be fatal [221][222][223][224]. Misuse of MDMA in crowded conditions with a high ambient temperature, physical activity, and dehydration, i.e., under conditions that MDMA is often used at "dance parties", may all contribute to increase the hyperthermic response.…”
Section: Mdma-induced Acute Human Peripheral Symptoms a Special Focumentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that body temperature may reach up to 43°C, which can be fatal [221][222][223][224]. Misuse of MDMA in crowded conditions with a high ambient temperature, physical activity, and dehydration, i.e., under conditions that MDMA is often used at "dance parties", may all contribute to increase the hyperthermic response.…”
Section: Mdma-induced Acute Human Peripheral Symptoms a Special Focumentioning
confidence: 99%
“…More severe acute effects include acute panic disorder and psychosis, arrhythmias and cardiovascular collapse with histological postmortem changes ranging from contraction band necrosis to individual myocyte necrosis, severe hyperpyrexia, liver failure accompanied by foci of individual cell necrosis to centrilobular necrosis and microvascular steatosis, acute renal failure with histological tubular necrosis, rhabdomyolysis and multi-organ failure, disseminated intravascular coagulation, hyponatremia with cerebral edema, the 5-HT syndrome, and sudden death [174,211,222,224,232,233]. In addition, potentially fatal neurological effects can occur following MDMA ingestion, including subarachnoid hemorrhage, intracranial hemorrhage or cerebral infarction, and cerebral venous sinus thrombosis [174,211,231].…”
Section: Mdma-human Acute Toxicitymentioning
confidence: 99%
“…Thus, the myoglobin staining results might underpin the hypothesis, causing relevant muscle damage due to shivering caused by raised body temperature, and seemed to be associated with prolonged agony phases of death, which is explainable by regular and repeated consumption rather than heavy single doses of METH [ 28 ]. Of course, muscle protein staining in kidneys of drug abusers is not associated with METH alone, as there are post-mortem and clinical case reports on MOR and ‘ecstasy’ intoxications as well [ 29 – 31 ]. Nonetheless, METH abuse is becoming an increasingly common cause of rhabdomyolsis in clinical settings [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur finden sich 2 ähnlich gelagerte Fallberichte [6,7]. In beiden Fällen handelte es sich um schwere, lebensbedrohliche Intoxikationen, die nach intensivmedizinischer Therapie überlebt wurden.…”
Section: Literaturunclassified